Benefits of Immersive Instruction Practices and Virtual Reality Technologies for EFL and ESL instruction (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
EFL (English as a Foreign Language) courses sometimes struggle to bring the authenticity of language to their students. Similar circumstances can occur in situations with ESL (English as a Second Language) students that return to a home that does not speak English. Some countries attempt to remedy this by bringing in native English speakers to co-teach EFL classes. Immersive education functions at its best when students are able to interact with their peers in a low-stakes environment. At the University of Toledo, there is a program in place where Japanese exchange students can interact with native English speaking students during a lunch period. Virtual reality headsets could be used to recreate this program without having to travel overseas.
Keywords: virtual reality; immersive instruction; VR; immersion benefits; EFL